The influence of narratives on women’s participation in security analytical frameworks - Pamela Pirateque-Perdomo; Ángela Gabriela Ramírez-Muñoz; Uriel Antonio Sánchez-Adarraga (Revista Científica General José María Córdova)
Women's participation in security has been limited by stereotypes legitimized through narratives and figures about how they "should be" and the fields they can access. This paper seeks to show the influence of gender-based narratives on security analytical frameworks based on understanding security, securitization processes, and feminism. Thus, a qualitative methodology with a grounded theory design is used, which, together with a literature review, exposes the need to include extended security approaches that delve deeper into the synergy of traditional and alternative approaches to threat management. The research determines that the participation of women in the Armed Forces, Intelligence, memory reconstruction, and peace makes it possible to redefine the narratives about their role in security while impacting the rigidity of agendas, academic spaces, and the international system itself.